The International Bank Lending Channel of Monetary Policy Rates and QE: Credit Supply, Reach-for-Yield, and Real Effects - Bernardo Morais; José-Luis Peydró; Jessica Roldán Pe\~na; Claudia Ruiz Ortega (Journal of Finance, 2019)
We identify the international credit channel by exploiting Mexican supervisory data sets and foreign monetary policy shocks in a country with a large presence of European and U.S. banks. A softening of foreign monetary policy expands credit supply of foreign banks (e.g., U.K. policy affects credit supply in Mexico via U.K. banks), inducing strong firm-level real effects. Results support an international risk-taking channel and spill overs of core countries' monetary policies to emerging markets, both in the foreign monetary softening part (with higher credit and liquidity risk-taking by foreign banks) and in the tightening part (with negative local firm-level real effects).
Additional information: This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions.
Keywords: E52; E58; G01; G21; G28; 330; monetary policy; financial globalization; quantitative easing (QE); credit supply; risk-taking; foreign banks